2010
DOI: 10.1152/ajpregu.00484.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-altitude hypoxia on the hormonal response to hypothalamic factors

Abstract: Acute and chronic exposure to high altitude induces various physiological changes, including activation or inhibition of various hormonal systems. In response to activation processes, a desensitization of several pathways has been described, especially in the adrenergic system. In the present study, we aimed to assess whether the hypophyseal hormones are also subjected to a hypoxia-induced decrease in their response to hypothalamic factors. Basal levels of hormones and the responses of TSH, thyroid hormones, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 42 publications
4
40
1
2
Order By: Relevance
“…2h). Because hypoxia can affect the secretion of thyroid hormones and can also cause changes in plasma levels of thyroxin [20][21][22], we tested whether the combination of SU5416 plus administration of thyroxin (however, without hypoxia) caused pulmonary vascular remodelling and PH. Our data demonstrate that chronic administration of thyroxin alone only causes mild PH in SU5416-treated rats ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…2h). Because hypoxia can affect the secretion of thyroid hormones and can also cause changes in plasma levels of thyroxin [20][21][22], we tested whether the combination of SU5416 plus administration of thyroxin (however, without hypoxia) caused pulmonary vascular remodelling and PH. Our data demonstrate that chronic administration of thyroxin alone only causes mild PH in SU5416-treated rats ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also shown that prolonged exposure to high-altitude hypoxia (3-4 days at 4350 m) does not affect the hypophyseal response to hypothalamic hormones. 104 Human chorionic gonadotropin hormone (hCG) acts on Leydig cells in the luteinizing hormone receptors. At HA (4340 m), low urinary excretion of testosterone after intramuscular injection of 2500 IU hCG has been observed.…”
Section: Testosterone In Men and Adaptation To Altitudementioning
confidence: 99%
“…Many factors have been proposed to modify the hormone levels in hypoxia, but most theories are still speculative. We conclude that exposure to acute hypoxia induces various changes in hormonal levels, but the hypophyseal response to hypothalamic factors does not appear to be blunted [ 30 ].…”
Section: Hormonal Response To Hypothalamic Factorsmentioning
confidence: 68%
“…[ 18 ] exposed to 4,350 m and a blunted response to GHRH was found in some subjects [ 30 ]. The concentration of IGF-1 was elevated [ 54 ] or unchanged [ 30 ] at high altitude while the binding protein IGFBP-3 was unchanged [ 30 , 54 ]. However, in subjects exposed for 3 weeks at 6,542 m, IGF-1 was normal [ 70 ], as well as in marathon runners at 4,000 m [ 113 ].…”
Section: Growth Hormonementioning
confidence: 99%
See 1 more Smart Citation